Atmospheric dispersion of natural carbon dioxide emissions on Vulcano Island, Italy. Issue 7 (17th July 2014) - Granieri, D.; Carapezza, M. L.; Barberi, F.; Ranaldi, M.; Ricci, T.; Tarchini, L.
Abstract La Fossa quiescent volcano and its surrounding area on the Island of Vulcano (Italy) are characterized by intensive, persistent degassing through both fumaroles and diffuse soil emissions. Periodic degassing crises occur, with marked increase in temperature and steam and gas output (mostly CO2) from crater fumaroles and in CO2 soil diffuse emission from the crater area as well as from the volcano flanks and base. The gas hazard of the most inhabited part of the island, Vulcano Porto, was investigated by simulating the CO2 dispersion in the atmosphere under different wind conditions. The DISGAS (DISpersion of GAS) code, an Eulerian model based on advection‐diffusion equations, was used together with the mass‐consistent Diagnostic Wind Model. Numerical simulations were validated by measurements of air CO2 concentration inside the village and along the crater's rim by means of a Soil CO2 Automatic Station and a Tunable Diode Laser device. The results show that in the village of Vulcano Porto, the CO2 air concentration is mostly due to local soil degassing, while the contribution from the crater gas emission is negligible at the breathing height for humans and always remains well below the lowest indoor CO2 concentration threshold recommended by the health authorities (1000 ppm). Outdoor excess CO2 maxima up to 200 ppm above local background CO2 air concentration are estimated in the center of the village and up to 100 ppm in other zones. However, in some ground excavations or in basements the health code threshold can be exceeded. In the crater area, because of the combined effect of fumaroles and diffuse soil emissions, CO2 air concentrations can reach 5000–7000 ppm in low‐wind conditions and pose a health hazard for visitors.